Pengaruh Kualitas Pelaporan Keuangan Dan Sustainability Reporting Pada Efisiensi Investasi - Vitriani, Ni Putu Lisna; Budiasih, I. G. A. N. (E-Jurnal Akuntansi; Vol 28 No 1 (2019), 2019)
The purpose of this study is to obtain empirical evidence regarding the effec of financial reporting quality and Sustainability Reporting on investment efficiency. This research was conducted on all non-financial companies listed on the Indonesia Stock Exchange in 2015-2017. The sampling technique used in this study was a purposive sampling. The samples taken were 16 companies with a total sample observation of 48 in 3 years. The data analysis technique used is Multiple Linear Regression. Based on the results of the study it is known that the higher the financial reporting quality of a company, the higher the level of efficiency of the company's investment and it is known that Sustainability Reporting has no effect on the efficiency of the company's investment. The results of this study are the practice of stakeholder theory and agency theory carried out by the company to maintain the long-term operational sustainability of the company. Keywords : Financial reporting quality, Sustainability Reporting, investment efficiency.